Regulation of the cytokine profile of NK cells by the microenvironment factors typical for pregnancy - P. V. Grebenkina; V. A. Mikhailova; O. N. Bespalova; S. A. Selkov; D. I. Sokolov (Медицинская иммунология, 2025)
Decidual NK cells exhibit distinct phenotypic and functional characteristics as compared to peripheral NK cells. However, the mechanisms underlying development of these unique properties remain poorly understood. The cells in microenvironment are known to exert both direct and indirect influence on NK cells within uterus, modulating their level of “aggressiveness” towards fetal tissues, including trophoblasts. Cytokine release presents a remote regulatory tool for the NK cells. Trophoblasts produce cytokines like as other components of the microenvironment. These cytokines bind the receptors on surface of target cells thud changing the behavior of NK cells. As a result, NK cells may release the own cytokines, which, in turn, influence the behavior of other cells. As mentioned above, there is a lack of data on causes and mechanisms behind the changes in characteristics of NK cells in uterus. Nevertheless, this data can lay the foundation for designing a more accurate cellular model of interactions between fetal cells and maternal immune system. Moreover, it may serve as a basis for developing diagnostic tools for reproductive issues. The aim of our study was to investigate changes in cytokine profile of NK cells, in particular, their production of TNFα, TGF-β, IFNγ, RANTES, IL-10, and VEGF under the influence of cytokines associated with pregnancy, i.e., TNFα, IFNγ, TGF-β1, IL-15, IL-18, or IL-10. The levels of these cytokines in the culture media conditioned by NK cells were measured using flow cytometry. TGF-β1, produced by trophoblasts was found to have the ability of regulating cytokine secretion by NK cells. The levels of IFNγ, IL-10, and RANTES in the media derived from NK cell culture have been decreased under its influence. On the basis of these findings, one may propose the existence of a regulatory system that controls activity of NK cells via the cytokine network. These data suggest a potential for using TGF-β1 to model in vitro interactions between NK cells and trophoblasts.